The Use of Information and Communication Technology for Determining the Level Mobility in Joint in Physical Education of Students - V. Koryahin; O. Blavt (OVS LLC, 2018)
The study objective is tothe substantiation and implementation of modern ICT for improving the testing of mobility in the joints in physical education of students. The task of our work is the is the development of tools that will allow researchers in the sphere of physical training to determine parameters of flexibility with a high degree of accuracy and reliability.  Materials and methods. To solve the research tasks used the methods of comparing and contrasting are used and analysis, synthesis, abstraction, formalization and scientific modelling.  Results. The method of flexibility testing with the use of an electronic ruler was developed. Functioning of the electronic ruler is based on measuring changes of the electric capacitance formed on the surface of the dielectric substrate of metal electrodes when the student touches it with his hand in the course of the test task. When performing the test task, the subject of monitoring touches with the hand the ruler, which registers the exercise process and its outcome. The resulting signal is processed promptly by the signal transducer placed in the ruler. Then the digital signal enters the processor that ensures its further conversion and signal transmission to the personal computer.  Conclusions. The main results of the research-scientific substantiation and implementation of the developed technology and method of recording the results of measurements in the tests, which are aimed to assess the physical of mobility in the joints by using electronic ruler designed on the basis of modern ICT. We have developed and offer methods by means of which, with a high degree of accuracy, one can determine the level of flexibility. For the first time the possibility of their use in the practice in physical education of students is shown and this allows to provide the rapid obtaining of reliable test data.